2012
DOI: 10.1016/j.cell.2012.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Coordinated Epigenetic Regulation of Developmental Transitions in the Cardiac Lineage

Abstract: SUMMARY Heart development is exquisitely sensitive to the precise temporal regulation of thousands of genes that govern developmental decisions during differentiation. However, we currently lack a detailed understanding of how chromatin and gene expression patterns are coordinated during developmental transitions in the cardiac lineage. Here, we interrogated the transcriptome and several histone modifications across the genome during defined stages of cardiac differentiation. We find distinct chromatin pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
733
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(766 citation statements)
references
References 60 publications
33
733
0
Order By: Relevance
“…To predict potential enhancers, we then focused on those regions marked by K4me1 but not K4me3. Notably, the use of histone marks to accurately predict enhancers should still be regarded as work in evolution 25,30,31 , and in this study, technical assessment of our enhancer prediction method using ENCODE data 32 suggests a sensitivity and specificity range of 37-67% depending on cell line ( Supplementary Fig. 5, Supplementary Table 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To predict potential enhancers, we then focused on those regions marked by K4me1 but not K4me3. Notably, the use of histone marks to accurately predict enhancers should still be regarded as work in evolution 25,30,31 , and in this study, technical assessment of our enhancer prediction method using ENCODE data 32 suggests a sensitivity and specificity range of 37-67% depending on cell line ( Supplementary Fig. 5, Supplementary Table 3).…”
mentioning
confidence: 99%
“…We note that our study is not without limitations. For example, although previous studies have successfully used histone marks (particularly K4me1) to predict enhancers 25,30,31 , it is worth noting that while many enhancers exhibit these marks, the same marks could also be present in other regions that are not necessarily enhancers (for example, distal DNase I hypersensitive sites 61 ). In our study, technical validation of our enhancer prediction method benchmarking ENCODE histone mark data against known TFBSs yielded varying levels of enhancer prediction accuracy depending on cell line (Supplementary Table 3).…”
mentioning
confidence: 99%
“…In mammalian systems, a fraction of enhancers have been shown to be poised prior to activation (Creyghton et al 2010;Rada-Iglesias et al 2011;Wamstad et al 2012;Wang et al 2015). This may be because the primed state already resembles the poised state or because enhancer activation occurs in a more sequential fashion by multiple patterning signals.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of enhancers become active without going through a poised state during prior developmental stages (Bonn et al 2012;Choukrallah et al 2015). Only a small fraction of poised enhancers are usually activated during lineage development (Rada-Iglesias et al 2011;Bonn et al 2012;Wamstad et al 2012). Instead, many enhancers that are poised in a cell type are active in related cell types (Bonn et al 2012;Junion et al 2012;Wang et al 2015).…”
mentioning
confidence: 99%
“…Thus, the authors concluded that Meis1 promotes CM cell cycle exit and reduces regeneration potential by activating negative cell cycle regulator genes. Over 400 potential target genes of Meis1 have been identified in embryonic CM development [9]. Further investigation will be required to identify additional direct targets of Meis1 that orchestrate cell cycle exit in neonates and to study whether transient manipulation of Meis1 can induce heart regeneration in adult hearts after injury.…”
mentioning
confidence: 99%